Investigation of User's Behaviors in Paid On-street Parking in Istanbul - DEMİR, ABDULLAH (TURKISH CHAMBER CIVIL ENGINEERS, 2019)
Istanbul is a megacity with a population of approximately 15 million, motor vehicles of 3.875 million including 2.669 million passenger cars, and on-street parking exceeding 70 percent of charged- or free-on-street parking, or illegal parking. In this study, changes in on-street parking users' behavior in Istanbul were analyzed as hours, days, months, seasons and years with taking advantage of the car parking data for about last 8 years. Effects of fee increases and short-term free parking practices were also examined. As a result of the study; It was found that 20 percent of the day parking entry was between 09.00 and 11.00, the maximum transactions occurred on Wednesday the middle day of the week, both the minimum transactions and the longest average parking time took place on Sunday. In addition, the average parking duration of the vehicles in on-street parking was increased year after year, furthermore the occupancy (parking index) in European side was reached 86 percent between 14.00 and 15.00, and the average parking time was about 2 hours. In another important investigation, in that 0-15 minute free parking option applied on on-street parking was temporarily removed; there were a marked decrease in parking turnovers, and increase in a rate of collection, income per transaction and the average parking time. However, when the 0-15 minute-free parking option was reapplied, a significant increase in assessment and collection rate was observed and positive effects on payment behaviors of parking users were determined.
Keywords: Parking behavior; on-street parking; parking time and fee; 0-15 minute-free parking; CHOICE